Implementasi Model Blended Learning Tipe Flipped Classroom Berbantuan Video untuk Meningkatkan Keterampilan Berpikir Kreatif Peserta Didik - Ahmad Harjono; Talitha Gita Andani; I Wayan Gunada; Susilawati Susilawati (Postgraduate, University of Mataram, 2022)
This study aims to determine the improvement of students' creative thinking skills through a video-assisted blended-flipped classroom model on work and energy materials. This study uses a quantitative approach. The research was carried out at SMA-IT Abu Hurairah Mataram in the 2nd semester of the 2021/2022 academic year. The research subjects were 32 students of X MIA 2. The instrument used is a test of creative thinking skills on work and energy materials. The results showed that the N-Gain scores of students on the aspects of fluency, flexibility, originality, and elaboration were 0.91; 0.27; 0.13; and 0.40 respectively. The average N-Gain score is 0.41 in the medium category. Thus, it can be concluded that the video-assisted blended-flipped classroom model can improve students' creative thinking skills